2022
DOI: 10.1101/2022.04.04.486950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Talin-drug interaction reveals a key molecular determinant for biphasic mechanical effect: studied under single-molecule resolution

Abstract: Talin as an adhesion protein, exhibits a strong force-dependent structure-function dynamics. Being a mechanosensitive focal adhesion (FA) protein, talin might interact to several FA targeting drugs; however, the molecular mechanism of talin-drug interactions remains elusive. Here we combined magnetic tweezers and molecular dynamics (MD) simulation to explore mechanical stability of talin with three drugs based on their talin specificity. Interestingly, our study revealed that talin displays a bimodal force dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…For example, docetaxel showed promising results inhibiting talin2 expression in a gastric cancer MKN45 cell line [171]. Moreover, several studies in vitro suggest anthocyanins, found in natural products like dark fruits and vegetables, as potential regulators of talin-integrin interaction leading to decreased tumor growth and cancer invasion [130,172].…”
Section: Talin and Integrin As Targets For Anti-cancer Therapiesmentioning
confidence: 99%
“…For example, docetaxel showed promising results inhibiting talin2 expression in a gastric cancer MKN45 cell line [171]. Moreover, several studies in vitro suggest anthocyanins, found in natural products like dark fruits and vegetables, as potential regulators of talin-integrin interaction leading to decreased tumor growth and cancer invasion [130,172].…”
Section: Talin and Integrin As Targets For Anti-cancer Therapiesmentioning
confidence: 99%